The Use of Students’ Oral Presentation in Enhancing Students’ Response in Teaching Reading - Zahratul Fikni; Ari Prasetya Ningrum (Humanitatis : Journal of Language and Literature, 2021)
Abstract: This study was aimed to know is there an effect of the use students’ oral presentation in enhancing students’ response in teaching reading . The research design of this study used pre-experimental in one group pretest – posttest design to know students’ response in teaching reading. Pre-test was administrated at the first meeting before teaching them by using each of the defined techniques for the students and post-test was given to the students at the same test after completing the treatment. Then, the researcher analyzed and compared the result of the pre test and posts test to measure the independent variable. The participants of the research were the eleventh grade of SMAN 1 Suralaga, consists of 35 students. The research instrument used by the writer was oral question. The researcher asked the students to give respond based on the text given. This was aimed at knowing the students respond toward the reading text. After the data were collected, the researcher then analyzed them by using t test formula. The finding of the research showed that: mean score of pre test was 15.22, while mean score of post test was 20.87, and observed was 6.94. the table with df=n-1 (35-1=34) and significance level at 0.05 was 2.31. It is means that the treatment by using students oral presentation in enhancing students’ respond in reading text, there was a positive effect to students’ response in teaching reading